2021
DOI: 10.1080/10942912.2021.1960371
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and gel properties of heat-induced pasteurized liquid egg white gel: effect of alkyl chain length of alcohol

Abstract: The influence of alcohols with different alkyl chain length (methanol, ethanol and propanol) on the physicochemical properties (turbidity, surface hydrophobicity, exposed and total free sulfhydryl groups, denaturation temperature; T m ) of pasteurized liquid egg white (PLEW), including gel properties (gel hardness and expressible liquid) and microstructure of heat-induced PLEW gel prepared at 75°C were studied. The results showed that alkyl chain length of alcohol and alcohol concentration had no impact on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…Nonetheless, from the observation, we can confirm that the PF-127, P-407, and combined PF-127 + P-407 forms optimized gel formation at 18 wt%, 19 wt%, and 9:10 wt%, respectively. Thus, this evidence confirmed that in the case of poloxamerbased hydrogel, the molecular weights don't significantly impact the gelation temperature [42,43]. Furthermore, all these compositions exhibit a smooth sol-to-gel transformation at 28℃ to 37℃, which is crucial for the internal in-situ application.…”
Section: Optimization Of Gelation Temperaturesupporting
confidence: 74%
“…Nonetheless, from the observation, we can confirm that the PF-127, P-407, and combined PF-127 + P-407 forms optimized gel formation at 18 wt%, 19 wt%, and 9:10 wt%, respectively. Thus, this evidence confirmed that in the case of poloxamerbased hydrogel, the molecular weights don't significantly impact the gelation temperature [42,43]. Furthermore, all these compositions exhibit a smooth sol-to-gel transformation at 28℃ to 37℃, which is crucial for the internal in-situ application.…”
Section: Optimization Of Gelation Temperaturesupporting
confidence: 74%
“…Fourth, proteins in the homeopathic medicines should be present in denatured and/or partially denatured state (denatured proteins are unfolded proteins) as ethyl alcohol, a component of the homeopathic drug vehicle, denatures proteins partially or completely. The degree of denaturation depends on the concentration of alcohol and the characteristics of the proteins [55]. Incidentally, proteins have a tendency to form aggregates, especially in their denatured or partially denatured states [56].…”
Section: Experimental Support For the Hypothesis And Some Issuesmentioning
confidence: 99%
“…Alcohol (ethanol), a component of the drug vehicle, can denature proteins (partially or completely, depending on the concentration of alcohol and the characteristics of the proteins) by disrupting their tertiary structure [56]. Even vigorous shaking denatures proteins [57].…”
Section: What Is the Origin Of Microbial Lysates In Homeopathic Medic...mentioning
confidence: 99%